Classification and certification of medicinal substances used in the treatment of goiter based on their chemical composition (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this article, there are recommendations on the classification and certification of medicinal substances used in the treatment of goiter based on their chemical composition.